1999
DOI: 10.1210/jcem.84.4.5583
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Somatostatin Receptor Scintigraphy in Patients with Occult Ectopic Adrenocorticotropin Syndrome

Abstract: SRIF receptor scintigraphy (SRS) has been proposed for the localization of ectopic ACTH-secreting tumors responsible for Cushing's syndrome. However, in most cases reported, the tumors were also visible using conventional imaging. Therefore, the usefulness of SRS in localizing truly occult ectopic ACTH-secreting tumors remains unknown. We report the results of SRS in 12 patients with ectopic ACTH syndrome (EAS) and in whom the source of ACTH was occult at presentation despite carefully performed conventional i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…NETs express somatostatin receptors (SSTs), in particular subtype 2, and can be identified with SSTs scintigraphy with 111 In-pentetreotide octreoscan. In EAS patients, reported sensitivity of the diagnostic octreoscan varies between 25 and 80%, and this broad range may in part be explained by differences in imaging technique protocols (2,7,21,22). Furthermore, we found five patients with negative ACTH immunohistochemistry in our series (lungZ2 and PanNETZ3).…”
Section: Discussionmentioning
confidence: 79%
“…NETs express somatostatin receptors (SSTs), in particular subtype 2, and can be identified with SSTs scintigraphy with 111 In-pentetreotide octreoscan. In EAS patients, reported sensitivity of the diagnostic octreoscan varies between 25 and 80%, and this broad range may in part be explained by differences in imaging technique protocols (2,7,21,22). Furthermore, we found five patients with negative ACTH immunohistochemistry in our series (lungZ2 and PanNETZ3).…”
Section: Discussionmentioning
confidence: 79%
“…Tabarin and coworkers (24) have questioned the additional utility of SSTR-based functional imaging, arguing that in most positive reported cases, the source of ectopic ACTH was already evident on conventional CT/MRI scans. They have shown the limited utility of SSTR imaging (octreotide-based SPECT imaging) over CECT in a carefully selected cohort of 12 patients with occult EAS on conventional imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale of high-dose dexamethasone suppression test (HDDST) is that corticotroph pituitary adenomatous cells in Cushing's disease retain partial sensitivity to glucocorticoids, whereas NETs responsible for EAS are fully resistant to exogenous glucorticoid suppression (157). Various thresholds have been proposed in the literature, with a percentage of urinary or serum cortisol suppression varying from 50% to 90% (170,171). However, some authors have shown an almost complete overlap between the response of EAT and corticotropic adenomas and have insisted on the impossibility of finding a discriminating threshold, especially in the case of well-differentiated NETs (172,172).…”
Section: (2) First-line Imaging Proceduresmentioning
confidence: 99%